Como a tutela jurídica ambiental afeta a concessão de crédito ao agronegócio - Oliveira, Tábata Boccanera Guerra de (2021)
Agribusiness is one of the most important sectors of the Brazilian economy and the financial institutions play a central role in granting credit to their activities. However, there are legal uncertainties related to the environmental risks assumed by financial institutions in such granting process. The first legal uncertainty that deserves to be highlighted concerns the lack of clarity in the application of some institutes of the Forest Code – federal legislation strictly related to the activities carried out by agribusiness. Since it came into force in 2012, such legislation has been subject of several questions in the judicial sphere, including the debate on its constitutionality. The second legal uncertainty highlighted is related to the lenders environmental liability. Especially after judgment of Special Appeal No. 650728/SC, by the rapporteur Minister Herman Benjamin, the concept of 'indirect polluter' has been substantially expanded, including those who finance or economically benefit from an activity that causes environmental damage. In this sense, questions about the possibility of co-responsibility of financial institutions for environmental issues have increased and much is discussed about the institution's duty of diligence in the context of its risk management to avoid such co-responsibility. Given this scenario, the purpose of this paper is to understand how environmental legal protection, which involves said uncertainties, affects the granting of credit to agribusiness. For this purpose, exploratory and semistructured interviews were carried out with five banks in order to assess the main challenges in the scope of credit granting and understand how such challenges could be faced, comparing such data with the literature review and triangulating the data with the selected jurisprudence. The results of this paper demonstrate that the extensive regulation and legal uncertainties greatly affect the granting of credit, increasing the cost of compliance and the time of operation and negotiation of contracts, which, ultimately, makes the access to credit difficult or impossible. As a result, it is clear that in many cases, there is a preference of borrowers for credits whose concession process is less regulated and less rigorous, and the intended purpose of environmental protection by the legislation ends up not being achieved, as banks will not have the obligation to check the environmental conditions within the scope of that operation.